The recurrent nuclear activity of Fornax A and its interaction with the cold gas. Issue Volume 15:Issue S359(2020) (March 2019) - Maccagni, F. M.; Serra, P.; Murgia, M.; Govoni, F.; Morokuma-Matsui, K.; Kleiner, D.
Abstract: Sensitive (noise ∼16 μ Jy beam −1 ), high-resolution (∼10″) MeerKAT observations of show that its giant lobes have a double-shell morphology, where dense filaments are embedded in a diffuse and extended cocoon, while the central radio jets are confined within the host galaxy. The spectral radio properties of the lobes and jets of reveal that its nuclear activity is rapidly flickering. Multiple episodes of nuclear activity must have formed the radio lobes, for which the last stopped 12 Myr ago. More recently (∼3 Myr ago), a less powerful and short (≲1 Myr) phase of nuclear activity generated the central jets. The distribution and kinematics of the neutral and molecular gas in the centre give insights on the interaction between the recurrent nuclear activity and the surrounding interstellar medium.